Electromagnetic fields and EEG spiking rate in patients with focal epilepsy. Issue 4 (April 2015) - Curcio, Giuseppe; Mazzucchi, Edoardo; Marca, Giacomo Della; Vollono, Catello; Rossini, Paolo Maria
Highlights Spiking activity tended to be slightly reduced by exposure to mobile phones. EEG Gamma band and interhemispheric connectivity increase as a consequence of exposure to mobile phones. Using mobile phones does not increase risk of incoming seizures in epileptics.